The red book - Lehman, Barbara (Boston : Houghton Mifflin, 2004)
A book about a book, a magical red book, without any words, and the friendship that develops around it.
Keywords: Books -- Juvenile fiction; Friendship -- Juvenile fiction; Books -- Fiction; Friendship -- Fiction; Stories without words